Randomized Trial of Machine Perfusion Versus Cold Storage in Recipients of Deceased Donor Kidney Transplants with High Incidence of Delayed Graft Function - Tedesco-Silva, Helio; Offerni, Juliano Chrystian Mello; Carneiro, Vanessa Ayres; Paula, Mayara Ivani de; David Neto, Elias; Lemos, Francine Brambate Carvalhinho; Moura, Lúcio Roberto Requião; Silva Filho, Alvaro Pacheco e; Cunha, Mirian de Fátima de Morais; Silva, Erica Francisco da; Miorin, Luiz Antonio; Demetrio, Daniela Priscila; et al. (Wolters Kluwer, 2017)
Background. This study compared the use of static cold storage versus continuous hypothermic machine perfusion in a cohort of kidney transplant recipients at high risk for delayed graft function (DGF). Methods. In this national, multicenter, and controlled trial, 80 pairs of kidneys recovered from brain-dead deceased donors were randomized to cold storage or machine perfusion, transplanted, and followed up for 12 months. The primary endpoint was the incidence of DGF. Secondary endpoints included the duration of DGF, hospital stay, primary nonfunction, estimated glomerular filtration rate, acute rejection, and allograft and patient survivals. Results. Mean cold ischemia time was high but not different between the 2 groups (25.6 ± 6.6 hours vs 25.05 ± 6.3 hours, 0.937). The incidence of DGF was lower in the machine perfusion compared with cold storage group (61% vs. 45%, P = 0.031). Machine perfusion was independently associated with a reduced risk of DGF (odds ratio, 0.49; 95% confidence interval, 0.26-0.95). Mean estimated glomerular filtration rate tended to be higher at day 28 (40.6 ± 19.9 mL/min per 1.73 m2 vs 49.0 ± 26.9 mL/min per 1.73 m2; P = 0.262) and 1 year (48.3 ± 19.8 mL/min per 1.73 m2 vs 54.4 ± 28.6 mL/min per 1.73 m2; P = 0.201) in the machine perfusion group. No differences in the incidence of acute rejection, primary nonfunction (0% vs 2.5%), graft loss (7.5% vs 10%), or death (8.8% vs 6.3%) were observed. Conclusions. In this cohort of recipients of deceased donor kidneys with high mean cold ischemia time and high incidence of DGF, the use of continuous machine perfusion was associated with a reduced risk of DGF compared with the traditional cold storage preservation method.